Do older patients feel able to cope with illness following telephone consultations? A multi-practice survey in the UK - Jiwa, Moyez; Freeman, J.; Coleman, M.; Joesbury, H. (LibraPharm, 2005)
Background: Worldwide, patients are offered a telephone consultation as a first point of access to a health care professional. Whilst older patients form a significant proportion of callers, this group has expressed reservation about consultations that preclude a physical examination. Objective: This study compares how two groups of patients (< 70 years, ≥ 70 years) perceive their ability to cope with illness following a telephone consultation. Methods: Nine hundred and fifty-six patients from deprived inner city areas receiving telephone consultations with a General Practitioner (GP)/Family doctor or nurse at five practices in South Yorkshire, UK were surveyed within 24h of the consultation. A 49% response rate was achieved; the mean age of respondents in the respective groups was 78.5 years and 48 years. The questionnaire included the Patient Enablement Instrument (PEI), a self-reported measure of patients' ability to cope with illness and supplementary questions on access to GPs in the practice. Results: There was a low response rate from younger patients and males in particular. Ethnic minority groups were hardly represented among the respondents. How ever, scores on the PEI following telephone consultations were no different between older and younger respondents (Mann–Whitney U test, p = 0.56). Regression analysis with PEI scores as the dependent variable and fitting age and differences in responses to the questionnaire as explanatory variables yielded an R2 of 0.02 suggesting that ‘age’ per se was a poor predictor of ‘enablement’. Conclusions: These data support an inclusive policy in the provision of telephone access to health care professionals in primary care. We conclude that older patients are not disadvantaged by consulting a primary care professional by telephone.